Pengaruh Tingkat Pendidikan terhadap Kesejahteraan Masyarakat di Desa Bube Baru Kecamatan Suwawa Kabupaten Bone Bolango Provinsi Gorontalo - Windrawati Mamui; Meyko Panigoro; Boby Rantow Payu; Roy Hasiru; Agil Bahsoan (Journal Innovation In Education, 2025)
This study aimed to determine the influence of education level on community welfare in Bube Baru Village, Suwawa Sub-District. This quantitative research used primary data obtained from the distribution of questionnaires to 56 people in Bube Baru Village. The data in this study were analyzed using simple linear regression. Based on the analysis, education level influenced the community’s welfare in Bube Baru Village, Suwawa Sub-District. Partially, the level of education significantly influenced the community’s welfare in Bube Baru Village, Suwawa Sub-District. The influence (partial) of the education level variable on the community’s welfare was 63,1%, and unexamined variables influenced 36,9%.